2022
DOI: 10.1111/lam.13671
|View full text |Cite
|
Sign up to set email alerts
|

Residual concentrations of antimicrobial growth promoters in poultry litter favour plasmid conjugation among Escherichia coli

Abstract: Considering that plasmid conjugation is a major driver for the dissemination of antimicrobial resistance in bacteria, this study aimed to investigate the effects of residual concentrations of antimicrobial growth promoters (AGPs) in poultry litter on the frequencies of IncFII‐FIB plasmid conjugation among Escherichia coli organisms. A 2 × 5 factorial trial was performed in vitro, using two types of litter materials (sugarcane bagasse and wood shavings) and five treatments of litter: non‐treated (CON), herbal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…Others have reported the impact of donor strain background on plasmid transfer [ 69 , 74 , 80 , 81 ]. Plasmid transfer has been previously reported in poultry bedding material where conjugation frequencies varied depending on bedding or presence of inhibitory chemical residues [ 83 , 84 ]. Guan et al reported plasmid transfer but with a higher rate in chicken manure than compost where donor and recipient cell abundance was affected by compost temperature [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Others have reported the impact of donor strain background on plasmid transfer [ 69 , 74 , 80 , 81 ]. Plasmid transfer has been previously reported in poultry bedding material where conjugation frequencies varied depending on bedding or presence of inhibitory chemical residues [ 83 , 84 ]. Guan et al reported plasmid transfer but with a higher rate in chicken manure than compost where donor and recipient cell abundance was affected by compost temperature [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of residues of MON, lincomycin and virginiamycin increased the frequency of plasmid conjugation among E. coli in both types of litter materials (sugarcane bagasse and wood shavings). In addition, the conjugation frequencies were significantly higher in wood shavings compared to sugarcane bagasse in the presence of antimicrobial growth promoters [58].…”
Section: Cross-resistance and Co-selectionmentioning
confidence: 96%
“…The process of plasmid conjugation represents the main driver through which bacteria can transfer genes that confer resistance to other bacteria, contributing to the dissemination of cross-resistance to critically important antimicrobials. A recent study well documented the effects of residual concentrations of different antimicrobial growth promoters, including MON, in poultry litter on the frequencies of IncFII-FIB plasmid conjugation, which harbors genes conferring resistance to amphenicols, aminoglycosides, β-lactams, macrolides, tetracyclines, trimethoprim and sulphonamides [57] among Escherichia coli (E. coli) organisms [58]. The presence of residues of MON, lincomycin and virginiamycin increased the frequency of plasmid conjugation among E. coli in both types of litter materials (sugarcane bagasse and wood shavings).…”
Section: Cross-resistance and Co-selectionmentioning
confidence: 99%